Tobacco Smoking Modifies the Association between Hormonal Factors and Lung Cancer Occurrence among Post-Menopausal Chinese Women - Jin, Kexin; Wu, Ming; Zhou, Jin-Yi; Yang, Jie; Han, Ren-Qiang; Jin, Zi-Yi; Liu, Ai-Min; Gu, Xiaoping; Zhang, Xiao-Feng; Wang, Xu-Shan; Su, Ming; Hu, Xu; et al. (Translational oncology, 2019)
Inconsistent evidence has been reported on the role of female hormonal factors in the development of lung cancer. This population-based case–control study evaluated the main effect of menstrual/reproductive factors on the risk of lung cancer, and the effect modification by smoking status. Multivariable unconditional logistic regression models were applied adjusted for age, income, education, county of residence, body mass index, smoking status, pack-years of smoking, and family history of lung cancer. Among 680 lung cancer cases and 1,808 controls, later menopause (at >54 vs. <46 years old) was associated with increased risk of lung cancer (SBOR, semi-Bayes adjusted odds ratio = 1.61, 95% PI, posterior interval = 1.10–2.36). More pregnancies (2 or 3 vs. 0 or 1) was associated with decreased risk (SBOR = 0.71, 95% PI = 0.53, 0.95). Ever being a smoker and having two or fewer pregnancies in one's lifetime could jointly increase the odds of lung cancer (RERI, relative excess risk due to interaction = 1.71, 95% CI = 0.03, 3.38). An increased number of ovulatory cycles was associated with increased risk of lung cancer (SBOR for 13 ovulatory cycles = 1.02, 95% CI = 1.00+, 1.04).